Pelatihan Inovasi Pemanfaatan Limbah Gedebog Pisang Produk Komersil - Lailal Gusri; Bambang Irawan; Hadrah; Anggrika Riyanti; Monik Kasman; M. Zahari MS; Hendi Matalata; Emelda Raudhati; Syabawaihi (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
Banana stems have benefits and can be processed into products with economic value. People sometimes ignore banana stems. Waste that is thrown away requires processing to reduce the amount of waste in the environment. The purpose of community service is to innovate to utilize banana stem waste into commercial products. The results of the community service are chips products that have characteristic flavors from the mixture. The community's response after participating in the training and eating the chips product: 1) opening up home business opportunities for the community in RT 03, Talang Banjar Village. 2) reducing waste from banana stems that are thrown into the environment. 3) providing useful knowledge and training to the community in RT 03, Talang Banjar Village.